Current evidence on chloroquine and hydroxychloroquine and their role in the treatment and prevention of COVID-19 - Mpofu, Rephaim; Banda, Clifford; Gunter, Hannah; Mondleki, Enkosi; Tatz, Gayle; Sinxadi, Phumla; Cohen, Karen; Barnes, Karen; Blockman, Marc (My University, 2020)
Although chloroquine and hydroxychloroquine have not yet been shown to be safe or effective for the treatment or prevention of COVID-19, regulatory agencies in some countries have authorised their use in Coronavirus disease 2019 (COVID-19) due to the lack of available interventions. Several large clinical trials are currently underway to investigate these agents as potential therapeutic options for COVID-19. Previous research against similar pathogens that cause severe acute respiratory syndrome and Middle East respiratory syndrome has identified chloroquine and hydroxychloroquine as possible antiviral candidates against SARS-CoV-2. Despite promising pre-clinical evidence, data have thus far failed to confirm their efficacy, and recent studies suggest potential dose-related cardiotoxicity and mortality. Close monitoring for cardiac conduction abnormalities is advised with higher-than-approved doses. Additional, robust evidence from randomised controlled trials and meta-analyses are required to make informed risk-benefit assessments. Finally, the off-label prescription of these agents should be judiciously considered, and any such use should be conducted within clinical trials, or under the Monitored Emergency Use of Unregistered and Investigational Interventions framework.
This is not the latest version of this article. The latest version has been uploaded as a separate article, please refer to it if you want to read it.
Keywords: COVID-19; chloroquine; hydroxychloroquine; SARS-CoV-2; MEURI; coronavirus